THE EFFECT OF CONSUMER TRUST AND EASE OF USE ON CONSUMER LOYALTY MEDIATED BY BRAND IMAGE ON TIX.ID APPLICATION USERS (STUDY ON FACULTY ECONOMIC OF BUSSINESUNIVERSITY OF BANDAR LAMPUNG STUDENTS) - Oktavia, Resti; Rama Putra Barusman, Andala (Jurnal Ilmiah Cano Ekonomos, 2025)
The purpose of this study is to analyze the influence of consumer trust variables and ease of use variables on consumer loyalty variables mediated by brand image on TIX.ID application users. This type of research is quantitative using primary data, obtained from respondents through questionnaires distributed online. The research participants were several students from the Faculties and Universities mentioned in the title, with a total of 280 respondents taken using random sampling techniques. Data were analyzed using PLS-SEM with the SmartPLS 4 application using validity tests, reliability tests, and hypothesis tests. The results of the study indicate that there is a significant relationship between consumer trust, ease of use, brand image, and consumer loyalty. Looking at the brand image variable that has a major role in mediating the relationship between the two variables X to variable Y. Overall, this study emphasizes that trust, ease of use, and brand image are interrelated and contribute to consumer loyalty.